2002
DOI: 10.1179/026708302225004784
|View full text |Cite
|
Sign up to set email alerts
|

Denitrogenation during vacuum induction melting refining Ni base superalloy using CaO crucible

Abstract: The denitrogenation behaviour during vacuum induction melting of Ni base superalloy using CaO crucible was studied, and the nitrogen solubility under different vacuum levels as well as Al and Ti addition amounts at 1873 K were also calculated. The experiment results show that Al addition had bene® cial effect, but Ti addition had adverse effect to denitrogenation. The increase of vacuum level is a powerful measure to accelerate the denitrogenation process. The denitrogenation mechanism has been discussed for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…7,8 Traditionally, most CaO crucibles were made from CaO powder and obtained by press molding or slip casting, and then sintered at high temperature. 9,10 However, when CaO clinker was used directly in the preparation process, the hydration problems caused by CaO resulted in difficulties in the production and the utilization of CaO crucibles. Furthermore, the related complicated manufacturing technology on free CaO contained materials also restricted the wide application of CaO crucibles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Traditionally, most CaO crucibles were made from CaO powder and obtained by press molding or slip casting, and then sintered at high temperature. 9,10 However, when CaO clinker was used directly in the preparation process, the hydration problems caused by CaO resulted in difficulties in the production and the utilization of CaO crucibles. Furthermore, the related complicated manufacturing technology on free CaO contained materials also restricted the wide application of CaO crucibles.…”
Section: Introductionmentioning
confidence: 99%
“…CaO crucible is also massively used in Ti‐Al alloys smelting and electronic materials smelting 7,8 . Traditionally, most CaO crucibles were made from CaO powder and obtained by press molding or slip casting, and then sintered at high temperature 9,10 . However, when CaO clinker was used directly in the preparation process, the hydration problems caused by CaO resulted in difficulties in the production and the utilization of CaO crucibles.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Especially for the CaO base refractory, it has great potential to remove high melting point inclusions, purifying molten steel. [18][19][20] In the past decades, the main research of refractory is the improvement of properties, and the potential functional role in the metallurgical was insufficiently appreciated. [21][22][23][24] In recent years, with the rising quality requirements of the steel production, the effect of refractory on inclusions has received more focus.…”
Section: Introductionmentioning
confidence: 99%
“…With researchers’ continuous studies of inclusions, it is found that the refractories, which were in full contact with the molten steel in the whole process, have an important influence on inclusions in steel 14–17 . Especially for the CaO base refractory, it has great potential to remove high melting point inclusions, purifying molten steel 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…However, VIM is the only vacuum melting method that uses a refractory crucible made of oxides such as SiO 2 , CaO, Al 2 O 3 , ZrO 2 , and MgO [ 7 , 8 ]. Unfortunately, the refractory is a contamination source of oxygen because the metal/refractory interface has a thermal mechanical infiltration and thermophysical effects, which lead to crucible disintegration [ 9 , 10 ]. Moreover, during the melting process, interfacial chemical reactions may occur between the ceramics and the active elements, such as Ti, Hf, Al, Cr, and so on.…”
Section: Introductionmentioning
confidence: 99%